2003
DOI: 10.1034/j.1600-0404.2003.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous protectant kynurenic acid in amyotrophic lateral sclerosis

Abstract: An increased CSF KYNA concentration in patients with bulbar onset of ALS and in patients with severe clinical status may indicate neuroprotective role of KYNA against excitotoxicity. The difference of KYNA concentration in CSF of patients with bulbar and limb onset of ALS suggests that these two variants of motor neuron disease may have different etiopathogenetic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 51 publications
1
56
1
Order By: Relevance
“…As described above, KYNA is increased in the CSF of ALS patients [72] although as previously mentioned this is insuffi cient to counter the effects of QUIN. Intracerebral administration of KYN by increasing endogenous KYNA concentrations might exert neuroprotective effects through blockade of the NMDA receptor through a NO and cGMP pathway in the cerebellum and hippocampus of rats [102] .…”
Section: Direct Evidencementioning
confidence: 79%
See 1 more Smart Citation
“…As described above, KYNA is increased in the CSF of ALS patients [72] although as previously mentioned this is insuffi cient to counter the effects of QUIN. Intracerebral administration of KYN by increasing endogenous KYNA concentrations might exert neuroprotective effects through blockade of the NMDA receptor through a NO and cGMP pathway in the cerebellum and hippocampus of rats [102] .…”
Section: Direct Evidencementioning
confidence: 79%
“…KYNA, QUIN in CSF and Serum from ALS Patients Ilzecka et al [72] showed that KYNA ( fi g. 1 ) concentrations in CSF were signifi cantly higher in patients with bulbar onset of ALS compared to controls and to patients with limb onset. Levels of KYNA in CSF were also higher in patients with severe clinical status compared to controls.…”
Section: Direct Evidencementioning
confidence: 99%
“…Recent studies have bridged a direct association between the KP and ALS (Guillemin et al 2005a). Ilzecka et al (2003) demonstrated that ALS patients with bulbar onset and severe clinical status had increased CSF KYNA levels. In contrast, serum KYNA levels were lower in patients with severe clinical status than in patients of mild clinical status or neurologically normal controls.…”
Section: Discussionmentioning
confidence: 97%
“…Neurotoxicity in ALS is, at least for a part, mediated through a mechanism involving NMDA receptor activation (Urushitani et al, 2001;Spreux-Varoquaux et al, 2002;Kanki et al, 2004). The CSF of ALS patients induces neurotoxicity through NMDA receptor activation (Ilzecka et al, 2003). In vitro studies showed that QUIN depolarizes the spinal motoneurons of newborn rats by activating NMDA receptors (Martin and Lodge, 1987;Mizuno, 1998).…”
Section: Relevance Of the Model To Other Inflammatory Brain Diseasesmentioning
confidence: 98%